Prenatal Selective Serotonin Reuptake Inhibitor Exposure, Depression, and Brain Morphology in Middle Childhood: Results From the ABCD Study - Allison L. Moreau; Michaela Voss; Isabella Hansen; Sarah E. Paul; Deanna M. Barch; Cynthia E. Rogers; Ryan Bogdan (Biological Psychiatry Global Open Science, 2023)
Background: Prenatal selective serotonin reuptake inhibitor (SSRI) exposure has been inconsistently linked to depression, and little is known about neural correlates. We examined whether prenatal SSRI exposure is associated with depressive symptoms and brain structure during middle childhood. Methods: Prenatal SSRI exposure (retrospective caregiver report), depressive symptoms (caregiver-reported Child Behavior Checklist), and brain structure (magnetic resonance imaging–derived subcortical volume; cortical thickness and surface area) were assessed in children (analytic ns = 5420–7528; 235 with prenatal SSRI exposure; 9–10 years of age) who completed the baseline Adolescent Brain Cognitive Development Study session. Linear mixed-effects models nested data. Covariates included familial, pregnancy, and child variables. Matrix spectral decomposition adjusted for multiple testing. Results: Prenatal SSRI exposure was not independently associated with depression after accounting for recent maternal depressive symptoms. Prenatal SSRI exposure was associated with greater left superior parietal surface area (b = 145.3 mm2, p = .00038) and lateral occipital cortical thickness (b = 0.0272 mm, p = .0000079); neither was associated with child depressive symptoms. Child depression was associated with smaller global brain structure. Conclusions: Our findings, combined with adverse outcomes of exposure to maternal depression and the utility of SSRIs for treating depression, suggest that risk for depression during middle childhood should not discourage SSRI use during pregnancy. Associations between prenatal SSRI exposure and brain structure were small in magnitude and not associated with depression. It will be important for future work to examine associations between prenatal SSRI exposure and depression through young adulthood, when risk for depression increases.